Prevalence of magnetic resonance imaging-defined atrophic and hypertrophic phenotypes of knee osteoarthritis in a population-based cohort - Roemer, Frank W.; Guermazi, Ali; Niu, Jingbo; Zhang, Yuqing; Mohr, Andreas; Felson, David T. (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective To describe the association of osteophytes with concomitant cartilage damage, assessed using semiquantitative magnetic resonance imaging (MRI), and to describe the prevalence of atrophic and hypertrophic phenotypes of tibiofemoral knee osteoarthritis (OA) in a population‐based cohort. Methods Participants of the Framingham Knee Osteoarthritis Study were examined with a 1.5T MRI system using triplanar intermediate‐weighted fat‐suppressed sequences. Cartilage and osteophytes were assessed using the Whole‐Organ Magnetic Resonance Imaging Score (WORMS). Overall prevalence of knees with severe cartilage damage and concomitant osteophyte status were described. Odds ratios for the likelihood of having severe cartilage damage according to osteophyte size were estimated using a logistic regression model. An additional analysis assessed knees according to phenotype in relation to radiographic OA status, with the atrophic phenotype being defined as knees with absent or only tiny osteophytes (WORMS grade ≤2 on a 0–7 scale) in all 10 tibiofemoral subregions but exhibiting severe cartilage damage, and the hypertrophic phenotype being defined as knees with large osteophytes (WORMS grade ≥5 on a 0–7 scale) but lacking substantial cartilage damage. Results In this study, 1,597 knees of 1,248 subjects were included. Of the 67 knees with large osteophytes, 54 (80.6%) exhibited severe cartilage damage. The risk of severe cartilage damage increased markedly with increasing osteophyte size. Twenty‐one knees (1.3%) showed an atrophic phenotype. Only 3 knees (0.2%) exhibited a hypertrophic phenotype. Conclusion The majority of knees with severe tibiofemoral cartilage damage exhibited moderate to large osteophytes. The larger the osteophyte, the more likely was the presence of severe cartilage damage. A minority of knees exhibited the atrophic phenotype, which also included knees without radiographic OA. The hypertrophic phenotype was extremely rare.